Comprehensive Review on Electric Propulsion System of Unmanned Aerial Vehicles - Joshi, Dhaval; Deb, Dipankar; Muyeen, S. M (Frontiers in Energy Research, 2022)
In recent years, electric unmanned areal vehicles (UAVs) are gaining popularity due to their capabilities in civil and military applications. The rationale is that UAVs can do more complex and risky tasks while maintaining mobility, safety, and cheap cost. UAVs are generally used for inspection and monitoring, search and rescue operation, delivery, precision agriculture, hobbyist applications, and many more. Due to a broad spectrum of applications, UAVs of various sizes and weights have evolved. UAVs have developed with the hybrid architecture of power supply incorporating batteries, fuel cells, solar photovoltaic systems, and supercapacitors for extended endurance and improved performance. The electric propulsion system is the central part of UAVs, which generates thrust to control and hover the UAVs in the air. The propulsion system includes an electric motor, electronic speed controller, power sources, and an energy management system for efficient operation. This paper presents an extensive and critical evaluation of state of the art on classifications, components of the electric propulsion system, the control strategy of electric motor, hybridization of power sources, and energy management system to identify research gaps and give insights exhortations for future research.